Differing In Vitro Potencies of Tocolytics and Progesterone in Myometrium From Singleton and Twin Pregnancies. (January 2016) - Arrowsmith, Sarah; Neilson, James; Bricker, Leanne; Wray, Susan
We compared the relaxant effect of 2 known tocolytics; indomethacin and atosiban and progesterone, on pregnant human myometrial spontaneous and oxytocin-induced contractions from singleton and twin pregnancies. All agents exerted a concentration-dependent relaxant effect on myometrial contractions. There was no significant difference in the concentration–response curves between singletons and twins for progesterone or indomethacin on spontaneous contractions or atosiban on oxytocin-induced contraction. Under oxytocin however, the concentration–response curves for indomethacin and progesterone were significantly shifted to the right for both amplitude of contraction ( P < .01) and activity integral ( P < .01). When compared to singleton myometrium however, the concentration–response curves were significantly shifted to the right in the twin myometrium group ( P < .05 progesterone and P < .001 indomethacin). We conclude that a greater concentration of progesterone and indomethacin is required to inhibit oxytocin-induced myometrial contractions in twins compared to singletons in vitro. The differences noted in the tissue pharmacologies may have implications for the successful prevention or inhibition of preterm labor in twin pregnancy.